Analisis Risiko Kesehatan Lingkungan Terhadap Paparan Debu Pada Pekerja Pasir di Kota Palembang - Dini arista putri; Rosyada, Amrina; Sari, Desri Maulina; Islamiati, Dian (LPPM Hang Tuah Pekanbaru, 2023)
Every workplace contains various potential hazards that can affect the health of workers, one of them is dust exposure. One of the dust exposures occurs in the working environment of the sand mine. Palembang City is an area flowed by the Musi River which is a place for sand mining in Palembang. This sand mining activity can pose a risk of exposure to dust such as PM10 and TSP. The purpose of this study was to analyze the environmental health risks due to dust exposure on sand collectors in Palembang. The EHRA method was used to take air samples at 19 measurement points to determine PM10 and TSP levels in the work area. Data collection was carried out using a questionnaire with 74 respondents. The results showed that there were 2 points at risk due to PM10 exposure with the RQ value at Depot 1 of 5.4 and Depot 2 of 2.7. Meanwhile, TSP levels do not pose a health risk to sand collectors in Palembang with an RQ value ≤ 1. So risk management is needed by reducing the PM10 concentration to a safe limit of 1.81 mg / m³.